VinJect: Toolkit for Penetration Testing and Vulnerability Scanning - AKBULUT, AKHAN (My University, 2018)
Penetration testing plays an important role in the development of secure software products and electronic systems. Sustainability of commercial systems is ensured through the regular scans of vulnerability. In this era where quality assurance and testing organizations become increasingly widespread, the effectiveness of the used tools and methods are critical. This article describes the architecture of the software named VinJect, which is developed for efficient penetration testing and vulnerability scanning. The primary goal of this application is to detect vulnerable locations in a shorter time with running in a multi-threaded structure. Our proposed application uses Wapiti and SQLmap applications’ services in the background. With user-friendly interfaces, it is also aimed to remove the bad user experience (UX) that these applications running on the command line have. In the tests we performed, WinJect was found to be more efficient in completing the vulnerability scans in a much shorter time.

Güvenilir yazılım ürünleri ve elektronik sistemlerin geliştirilmesinde sızma testi önemli rol oynamaktadır. Zaafiyet taramalarının düzenli olarak yapılması sayesinde, ticari sistemlerin sürdürülebilirliği sağlanmaktadır. Kalite güvence ve test firmalarının günümüzde yaygınlıklarını arttırdıkları bu dönemde, kullanılan araç ve yöntemlerin etkinlikleri çok kritiktir. Bu makalede etkin bir sızma testi ve güvenlik açığı taraması için geliştirilmiş VinJect ismindeki yazılımın mimarisi anlatılmaktadır. Amaç, çok iş parçacıklı yapıda çalışan bu uygulama ile zaafiyet barındıran yerlerin tespitinin daha kısa sürede yapılmasıdır. Önerdiğimiz uygulama, arka planda Wapiti ve SQLmap uygulamalarına ait servisleri kullanmaktadır. Kullanıcı dostu arayüzler ile çoğunlukla komut satırında çalışan uygulamaların verdiği olumsuz kullanıcı tecrübesinin (UX) ortadan kaldırılması hedeflenmiştir. Yaptığımız testlerde, WinJect'in daha etkin bir kullanım sunduğu ve zaafiyet taramalarını çok daha kısa sürede tamamladığı görülmüştür.
VinJect: Sızma Testi ve Güvenlik Açığı Taraması Aracı
Keywords: Penetrasyon Testi Aracı; Güvenlik Açığı Tespiti; Güvenlik; Penetration Testing Tool; Vulnerability Detection; Security